(untitled) (International Journal of Food and Nutritional Sciences, 2021)
In internet data packets are typically routed through various networks until they reach their destination. Currently, the majority of daily activities are conducted online using the internet. Due to the ease of internet access, anyone can share information with anyone else without any prerequisites. The design architecture of the internet does not perform security verification of the originality of each data packet. This lack of verification opens the door to various network security vulnerabilities, such as denial-of-service (DoS) attacks and man-in-the-middle attacks. A major threat to the internet is the DoS attack, characterized by explicit attempts by attackers to prevent legitimate users from accessing a service. This can include efforts to flood a network, thereby blocking legitimate network traffic, or disrupting connections between machines to prevent access to a service. Various detection techniques have been proposed by the research community to identify the origin of these attacks. This article proposes a traceback-based technique to identify the source of the attack.